Digital marketing training by Lazismu Medan City to increase the MSMEs competitiveness - Ahmad Afandi; Syahrul Amsari; Isra Hayati (Community Empowerment, 2023)
Digital marketing training is an important solution to increase the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the rapidly growing digital era. This community service aims to provide digital marketing training to MSMEs assisted by Lazismu, Medan City. Identification of partner problems is carried out through meetings with Lazismu leaders to understand the challenges MSMEs face after the Covid-19 pandemic. The training was conducted using interactive lecture and discussion methods, covering marketing strategies through social media, search engine optimization, quality content, and online brand management for 30 MSMEs assisted by Lazismu Medan City. Evaluation is done through a questionnaire to measure the effectiveness of the training. The evaluation results show participant satisfaction and increased knowledge and skills in digital marketing. This training helps MSMEs expand market reach, increase business visibility, and increase sales. In conclusion, digital marketing training effectively increases the competitiveness of MSMEs in the digital era and solves challenges faced after the Covid-19 pandemic.